Truffles—Tuber spp. - James M. Stephens (EDIS)
This document provides an overview of truffles (Tuber spp.), focusing on their biology, cultivation, and culinary use. It describes the characteristics of various truffle species, including the Perigord and white truffles, and outlines traditional and experimental methods of cultivation. The document also highlights the challenges of truffle farming and their high value in gourmet cuisine due to limited availability and specialized harvesting techniques. Original publication date May 1994